Sex differences in time trends of blood pressure among Swedish septuagenarians examined three decades apart: a longitudinal population study. Issue 7 (July 2017) - Joas, Erik; Guo, Xinxin; Kern, Silke; Östling, Svante; Skoog, Ingmar
Abstract : Objective: The aim of this study was to analyze the influence of birth cohort, sex and age on the trajectories of SBP and DBP in two birth cohorts of 70-year-olds, examined 3 decades apart and followed up at ages 75 and 79–80 years. Methods: Two population samples of 70-year-olds from Gothenburg, Sweden, were examined. The first, born in 1901–1902, was examined in 1971–1972 ( n  = 973). The second, born in 1930, was examined in 2000 ( n  = 509). Both samples were re-examined at ages 75 and 79–80 years. Results: We found that SBP and DBP were considerably lower in septuagenarian men and women born 1930 compared with those born 1901–1902, also when adjusting for antihypertensive treatment in different ways. The decline was especially pronounced in women. Blood pressure was higher in women than in men in the 1970s, whereas there were no sex differences in the 2000s. The age-related decline in SBP started earlier and was more accentuated in those born in 1930 than in those born in 1901–1902. Conclusion: Blood pressure decreased, and the age-related decline in SBP started earlier in septuagenarians examined in the 2000s compared with those examined in the 1970s. The decrease was especially pronounced in women and diminished the sex differences. Antihypertensive treatment only partly explained our findings, suggesting that other mostly unknown factors played an important role. Abstract : Supplemental Digital Content is available in the text